2021
DOI: 10.4314/sajas.v51i1.2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of guavira fruit (Campomanesia adamantium) peel extract on performance and meat quality of broilers

Abstract: This article assessed the performance, carcass yield, and meat quality of finishing broilers fed increasing levels of hydroethanolic extract of guavira fruit peel (HEGP) were assessed. A total of 480, three-weeks-old male broilers were randomly allocated to dietary levels of HEGP (0, 100, 200, 300, 400, and 500 mg/kg), with five replicates and 16 birds each. There was a quadratic effect of HEGP inclusion on weight gain (WG) and feed conversion ratio (FCR), with the greatest WG and FCR being calculated at level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Polyphenols and flavonoids, bioactive compounds found in the extract, are able to improve intestinal health, influence digestive processes and modulate the animal immune system and, consequently, may improve meat quality and poultry performance through reducing the lipid oxidation process by neutralizing oxidative stress. Diet supplementation with those bioactive compounds could drive similar or approximate results found when using performance-enhancing antibiotics (Lohmann et al, 2021).…”
Section: Other Biological Propertiesmentioning
confidence: 62%
See 1 more Smart Citation
“…Polyphenols and flavonoids, bioactive compounds found in the extract, are able to improve intestinal health, influence digestive processes and modulate the animal immune system and, consequently, may improve meat quality and poultry performance through reducing the lipid oxidation process by neutralizing oxidative stress. Diet supplementation with those bioactive compounds could drive similar or approximate results found when using performance-enhancing antibiotics (Lohmann et al, 2021).…”
Section: Other Biological Propertiesmentioning
confidence: 62%
“…One of these practices is the routine poultry use of low-dose antibiotics to manipulate the intestinal health of broiler chickens, enhancing nutrient absorption and assimilation, thus reducing feed costs, but which is also correlated with the development of bacterial resistance in humans. Thus, Lohmann et al (2021) aimed to assess the effects of guavira peel hydroethanolic extract (GPHE) on the performance and meat quality of broilers. Crescent concentrations of C. adamantium peel extract (0 to 500 mg/kg) were given to broilers in the finishing phase (from 21 to 42 days), and several parameters were assessed.…”
Section: Other Biological Propertiesmentioning
confidence: 99%
“…The latter investigators speculated that the low pH values of meat (primarily due to stress conditions before slaughter) seem to be responsible for the denaturation of protein myofibrils leading to low WHC in their study. Previously, Lohmann et al (2021) also reported that dietary guavira fruit (Campomanesia adamantium) peel extract (100, 200, 300, 400, and 500 mg/kg feed) reduced thigh muscle redness 15 min after slaughter. It has widely been known that myoglobin is responsible for the redness values of meats.…”
Section: Effect Of Plant-derived Products On Physical and Organolepti...mentioning
confidence: 91%
“…In most situations, polyphenols derived from plant products are expected to prevent or minimize the oxidation of myoglobin into metmyoglobin. However, the antioxidative functions of plant-derived polyphenols are impaired by their low bioavailability (Lohmann et al, 2021). This may explain the absent effect of herbal products on broiler meats' physical and chemical aspects.…”
Section: Effect Of Plant-derived Products On Physical and Organolepti...mentioning
confidence: 99%
“…Moreover, studies suggest that essential oils extracted from guavira fruit have antimicrobial activity against Staphylococcus aureus, Pseudomonas aeruginosa, and Candida albicans, and moderate activity against Escherichia coli (Coutinho et al, 2009;dos Santos et al, 2019). Lohmann et al (2021) observed that the dietary inclusion of 219 mg/kg of HEGP resulted in better feed conversion rate for broilers in the finishing phase. In this context, the use of natural additives in animal feed has become a feasible alternative to antibiotics because they protect the intestinal mucosa and favour digestion and absorption processes, which contributes to a balanced gut microbiota.…”
Section: Introductionmentioning
confidence: 99%